Gender and Age Segregation and Stratification in Criminal Collaborations - Carrington, Peter J. (Journal of quantitative criminology, 2016)
Objectives Assess gender and age segregation and stratification among co-offenders. Methods The population comprises co-offenders aged 5–75 in police-reported co-offenses in Canada, 2006–2009. Segregation is indicated by observed and inbreeding homophily, measured with cross-tabulations and log-linear distance models. Stratification is assessed with elaborations by crime type. Intersectionality of gender and age status is estimated with interaction terms in the log-linear models. Results Female and younger offenders are over-represented among co-offenders. Co-offending exhibits gender and age status homophily: same-gender dyads are approximately twice as frequent as mixed-gender, and same-age-status dyads are almost 7 times as frequent as mixed-age-status. Gender homophily varies by crime type, being stronger in robbery, aggravated assault, common assault, and minor theft, and weaker in serious drug crime and homicide, and (especially) sex crimes against children. Age homophily is strong in all types of crime. Gender and age homophily have a negative interaction: dyads comprising a female child or youth and an adult male occur 1.4 times as frequently as predicted from the main effects of gender and age status. Conclusions Female and younger offenders are not excluded from co-offending per se but, consistent with expectations from Blau’s (Inequality and heterogeneity. Free Press, New York, 1977 ) and Steffensmeier’s (Soc Forces 6:1010–1032, 1983 ) theories, they are segregated from co-offending with male and (especially) adult offenders. There was limited evidence of gender stratification, and no evidence of age stratification. The interaction of gender and age status in the segregation and stratification of co-offending attenuates their individual effects, contrary to expectations from feminist intersectionality theory and consistent with Blau’s ( 1977 ) theory.